Analysis of the Republic of Moldova's Relationship with the European Union in Light of the Eastern Partnership Index - Mircea BRIE (Analele Universităţii din Oradea. Relaţii Internaţionale şi Studii Europene, 2022)
In June 2022 the Republic of Moldova received the status of candidate country for membership of the European Union. In spite of the euphoria generated by this historic step, European integration seems to be a difficult and lengthy process. The result is nevertheless of considerable importance, but it raises the question: what has determined this development? Was it Republica Moldova’s proactive progress, or the geopolitical climate introduced after Russian aggression against Ukraine? Methodologically, we aim to analyze some of the indicators quantified in the Eastern Partnership Index during the period 2011-2021. We intend to identify the integrator level in three relevant measurable areas (and a couple of subareas): Management, Approximation and Linkage. From a methodological perspective, we propose the following levels of analysis: a. A contextualization of the RM's involvement in the EaP; b. An analysis of the EaP Index and the identification of integrator levels; and c. Generating an inductive response regarding the European path of the RM